Diabetic Ketoacidosis in Patients with Maturity-Onset Diabetes of the Young - Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes, 2024)
Maturity-onset diabetes of the young (MODY) is the most frequent monogenetic diabetes form. It is caused by mutations in genes important for the development and function of pancreatic beta-cells, resulting in impaired insulin secretion capacity. Up to now, 14 different types have been described. The inheritance pattern is autosomal dominant, leading to a strong family history with more than three affected generations. Young age at diagnosis and lack of pancreatic autoantibodies are further characteristics of MODY. The presence of diabetic ketoacidosis (DKA) was long regarded as an exclusion criterion for MODY. However, in recent years, several case reports on MODY patients presenting with DKA have been published. The present study aimed to give an overview of the current knowledge of DKA in MODY patients, with a collection of published case studies as a prerequisite for this review.
Keywords: DKA, ketosis; MODY; HNF4A; HNF1A; HNF1B; NEUROD1; CEL; PAX4; INS; ABCC8; KCNJ11